The horse soldiers [videorecording (DVD)] - Wayne, John, 1907-1979; Holden, William, 1918-1981; Towers, Constance; Sinclair, Harold, 1907-1966 (Western legends., 2001)
Colonel Marlowe is in command of a motley assortment of 1200 Union volunteers whose task-- and apparent suicide mission-- is to infiltrate 300 miles of Southern territory and destroy the most strategic rail route in the Confederacy. Marlowe's life is complicated by his ferocious running feud with the company's surgeon, Major Kendall.